1991
DOI: 10.1111/j.1600-0528.1991.tb00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary reasons for extraction of permanent teeth in Norway: changes from 1968 to 1988

Abstract: The purpose of the present study was to investigate time trends in primary reasons for extraction of permanent teeth in Norway from 1968 to 1988. Johansen studied reasons for extraction of 8757 teeth in 4216 patients during a 3-week period in 1968. Twenty years later a random sample of 500 Norwegian dentists provided particulars about all extractions carried out during a 2-week period. 350 dentists (70%) replied in 1988 but 96 of them had not extracted any teeth during the observation period. Reasons for extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
58
1
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 13 publications
8
58
1
6
Order By: Relevance
“…1,[7][8][9][10][11][12][13][14][15] These variations, however, are at least partly attributable to methodological differences. This is illustrated by comparison of the two Canadian studies.…”
Section: Discussionmentioning
confidence: 99%
“…1,[7][8][9][10][11][12][13][14][15] These variations, however, are at least partly attributable to methodological differences. This is illustrated by comparison of the two Canadian studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed the trend that periodontal disease was the most frequent reason for tooth extraction in patients over 45 years of age as shown in previous studies. 3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] Natural consequence of aging does not cause severe periodontal disease, and a small proportion of persons exhibit severe periodontitis in which tooth loss occurs. 22,23 Therefore, a large number of extractions might be extracted due to periodontal disease in a relatively small number of patients.…”
Section: Sex Age (Yr)mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] The main reasons for permanent tooth extraction differ among countries. Studies in many countries and some studies in small areas have shown that dental caries is the most common reason for tooth extraction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…대체적으로 OECD 국가에서 적어도 30세 이후에는 치주병이 치아발거 제1원인으로 요약할 수 있다 [2][3][4][5][6][7][8][9] . , 국제적인 비교도 활발하다 14) .…”
Section: )unclassified